Simultaneous removal of heavy metals from aqueous solutions by Equisetum diffusum D. Don - Ha, Nguyen Thi Hoang; Thom, Vu Thi (Vietnam Journal of Earth Sciences, 2019)
Equisetum diffusum D. Don was transplanted into solutions added with different concentrations of Mn, Zn, Cd, Pb, and As for 30 days in the laboratory experiment to assess the removal of these metals and their accumulation in the plant. The highest removal efficiency of Mn, Zn, Cd, Pb, and As from solutions by E. diffusum was 99.6, 97.9, 77.5, 85.3, and 61.9%, respectively. The highest daily removal efficiencies of heavy metals were obtained after 1 day of new solution addition. The highest concentrations of Mn, Zn, Cd, Pb, and As in the plant roots were 7230, 1490, 174, 1170, and 274 mg/kg-DW, respectively; those in the shoots were 1960, 566, 33.9, 308, and 108 mg/kg-DW. The bioconcentration factor (BCF) values for Mn, Zn, Cd, Pb, and As were 496, 406, 702, 463, and 191, respectively. The results of this study indicate that E. diffusum has the ability to remove simultaneously these metals from water, making it a potential species for phytoremediation of water contaminated with multiple heavy metals.